Strengthening English Language Learning Through an Independent Curriculum Approach - Ratna Rintaningrum; Arfan Fahmi; Kartika Nuswantara; Umi Trisyanti; Khanan Yusuf; Siti Zahrok (International Journal of Science and Society, 2023)
This research aims to investigate the effectiveness of the "Independent Curriculum" approach in strengthening English language learning. The Merdeka Curriculum, which emphasizes student autonomy and an interest-based learning approach, is applied to a number of high school students in Indonesia. The research method used is a qualitative method with observation, in-depth interviews, and document analysis as data collection instruments. The research results show that the Merdeka Curriculum approach is able to increase learning motivation, active involvement of students in the learning process, as well as students' English language skills, especially in the aspects of speaking and writing skills. In addition, students also show an increase in creativity and critical thinking skills. In conclusion, the Merdeka Curriculum approach offers an innovative and effective alternative in learning English, while supporting the formation of independent, creative and critical student character.